Tweeters, Woofers and Horns: The Complex Orchestration of Calcium Currents in T Lymphocytes - Nohara, Lilian L.; Stanwood, Shawna R.; Omilusik, Kyla D.; Jefferies, Wilfred A. (Frontiers in Immunology, 2015)
Elevation of intracellular calcium ion (Ca2+) levels is a vital event that regulates T lymphocyte homeostasis, activation, proliferation, differentiation, and apoptosis. The mechanisms that regulate intracellular Ca2+ signalling in lymphocytes involve tightly controlled orchestration of multiple ion channels, membrane receptors, and signalling molecules. T cell receptor (TCR) engagement results in depletion of endoplasmic reticulum (ER) Ca2+ stores and subsequent sustained influx of extracellular Ca2+ through Ca2+ release-activated Ca2+ (CRAC) channels in the plasma membrane. This process termed store-operated Ca2+ entry (SOCE) involves the ER Ca2+ sensing molecule, stromal interaction molecule 1 (STIM1), and a pore-forming plasma membrane protein, ORAI1. However, several other important Ca2+ channels that are instrumental in T cell function also exist. In this review, we discuss the role of additional Ca2+ channel families expressed on the plasma membrane of T cells that likely contribute to Ca2+ influx following TCR engagement, which include the IP3 receptors, the P2X receptors, the NMDA receptors, and the TRP channels, with a focus on the voltage-dependent Ca2+ (CaV) channels.